Palliative care practices in long term care facility for the elderly (Revista Brasileira Multidisciplinar, 2025)
Long Term Care Facilities for the elderly (LTCF) are institutions that must guarantee safe and healthy environment for their residents, which implies offering palliative care (PC) when necessary. The objective of this study was to analyze the daily PC practices offered by a multidisciplinary team in the context of LTCF. This is a qualitative study, carried out in an LTCF in Belo Horizonte, MG, with 12 professionals of the multidisciplinary team. Data were collected through semi-structured interviews and submitted to content analysis. The results shows that CP practices in the context of LTCF are configured around the organization of the routine and the environment for its development. The analysis revealed the importance of care centered on the patient's needs to ensure its quality and effectiveness. The organization of PC can favor the promotion of humanized assistance, capable of meeting physical, emotional, social and spiritual needs of the elderly, as well as their families. Furthermore, the work shared by the multidisciplinary team enhances results and maximizes the quality of care.
Keywords: palliative care; homes for the aged; aged; patient care team; institucionalization